Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/healthcare9111437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Patient-Selected Music Listening on the Pain and Anxiety of Patients Undergoing Hemodialysis: A Randomized Controlled Trial

Abstract: This study aimed to analyze the influence of patient-selected music listening on the pain and anxiety levels of hemodialysis patients after undergoing a vascular access operation. Methods: Sixty five patients were randomly assigned to the experimental group (n = 32) or the control group (n = 33). The experimental group was instructed to listen to their favorite music using headphones during their operations at the center. The control group underwent the operations without listening to any music. The pain measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…Lastly, through neurochemical modulation, music induces the release of endorphins, which can act as analgesics to minimize pain sensations [ 61 , 62 ]. A study examined the effect of listening to patient-selected music on the pain and anxiety levels of hemodialysis patients during vascular access operations [ 63 ]. The experimental group listened to their favorite music during their operations, while the control group did not.…”
Section: Other Alternative Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, through neurochemical modulation, music induces the release of endorphins, which can act as analgesics to minimize pain sensations [ 61 , 62 ]. A study examined the effect of listening to patient-selected music on the pain and anxiety levels of hemodialysis patients during vascular access operations [ 63 ]. The experimental group listened to their favorite music during their operations, while the control group did not.…”
Section: Other Alternative Methodsmentioning
confidence: 99%
“…The experimental group listened to their favorite music during their operations, while the control group did not. The experimental group had drastically reduced subjective pain levels, objective pain behaviors, and lower levels of subjective anxiety and anxiety states compared to the controls [ 63 ]. These results suggest that music medicine can be a useful clinical intervention to reduce pain and anxiety in hemodialysis patients [ 63 ].…”
Section: Other Alternative Methodsmentioning
confidence: 99%
“…Similarly, in a study with 65 dialysis patients, it was shown that participants who were listening to music during vascular access surgery had significantly lower perceived levels of pain than the control group [ 33 ]. In a similar study with 55 patients who underwent fistula surgery, patients who listened to music during the fistula surgery had significantly lower anxiety and better heart rate, respiratory rate, and oxygen saturation than the control group [ 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…When people listen to their desired music, it helps them reduce the feeling of pain possibly because music affects the autonomic nervous system and leads to emotional and physiological improvement [ 33 ]. Music therapy can lead to hemodynamic changes, such as reduced heart rate and blood pressure [ 24 ], while it increases positive emotions and reduces negative emotions [ 34 ] Additionally, it acts as an analgetic because it releases dopamine and endorphins, which, in turn, balances the autonomic nervous system [ 34 ].…”
Section: Reviewmentioning
confidence: 99%
“…Music benefit individuals both in health and disease. Several studies show that many painful conditions and disorders can be alleviated by music ( Düzgün and Karadakovan, 2021 ; Feneberg et al, 2021 ; Gauba et al, 2021 ; Kim and Jeong, 2021 ; Monsalve-Duarte et al, 2021 ; C. Wang and Tian, 2021 ). When a painful stimulus is applied to volunteers under control conditions while listening to their favorite songs, they report lower pain rating scores as music modulates pain responses in cortical regions, brainstem and spinal cord ( Dobek et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%